Stimulasi Perilaku Prososial Anak Usia Dini Melalui Permainan Tradisional Congklak - Revalyta Az zahra; Siti Kurniasih; Suryadi (ALMURTAJA: Jurnal Pendidikan Islam Anak Usia Dini, 2026)
This study aims to describe the stimulation of prosocial behavior in early childhood through the traditional congklak game. Early childhood is considered the golden age, a critical period that plays an important role in shaping children's future development. Despite its importance, various studies indicate that Indonesian children still face challenges in social-emotional development, which are further exacerbated by the dominance of individualistic digital games. This study employed a descriptive qualitative approach. The research subjects consisted of four early childhood children living in Rajabasa Lama Village, RT 04 RW 01. Data were collected through participant observation, interviews, and documentation. The findings revealed that the traditional congklak game effectively stimulated children's prosocial behavior, including patience in waiting for turns, honesty in following game rules, and sportsmanship in accepting defeat. In addition, the game encouraged positive social interactions among children. The study concludes that the traditional congklak game is an effective learning medium for stimulating prosocial behavior and fostering character development through direct social interaction during play activities.